2019
DOI: 10.4995/eurocall.2019.11500
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spanish Proficiency of Online Language Learners after Year 1

Abstract: <p>Online (OL) second language (L2) courses are becoming more widely offered in the United States; however, little information exists about the effectiveness of OL L2 courses beyond one semester or course. Therefore, the purpose of this study was to assess Spanish students’ oral proficiency after completing one year of OL only L2 courses. At the end of year one, students (<em>n</em>=65) completed the Versant exam, which scored overall level of oral proficiency as well as four sub-categories: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A decade later, three studies (Moneypenny & Aldrich, 2016;Moneypenny & Aldrich, 2018;Aldrich & Moneypenny, 2019) in particular supported the findings of Blake et al (2008) and took them a step further to compare fully online courses to on-ground courses. Not only did these studies also use the Versant test to specifically compare student oral language proficiency outcomes, they also largely concluded that students in fully online Spanish courses achieved equivalent oral proficiency outcomes as their peers in onground courses.…”
Section: Proficiency Development and Technology-mediated Language Ins...mentioning
confidence: 77%
See 2 more Smart Citations
“…A decade later, three studies (Moneypenny & Aldrich, 2016;Moneypenny & Aldrich, 2018;Aldrich & Moneypenny, 2019) in particular supported the findings of Blake et al (2008) and took them a step further to compare fully online courses to on-ground courses. Not only did these studies also use the Versant test to specifically compare student oral language proficiency outcomes, they also largely concluded that students in fully online Spanish courses achieved equivalent oral proficiency outcomes as their peers in onground courses.…”
Section: Proficiency Development and Technology-mediated Language Ins...mentioning
confidence: 77%
“…The effectiveness of online, blended, hybrid, or technology-enhanced language instruction for developing student language proficiency has been assessed in a variety of instructional contexts, including in blended/hybrid courses often with a succession of regular, ongoing technology-mediated tasks, as well as in more traditional courses that have a limited scope for technology or may not use it at all for language instruction (Plonsky & Ziegler, 2016). The field has also seen studies that compare student proficiency outcomes in fully on-ground language courses to those drawn from students in fully online courses (e.g., Aldrich & Moneypenny, 2019), the latter of which have been growing in popularity over the past decade as the technological possibilities expand. As these technologies and tech-enhanced instructional practices evolve, so too have our classrooms and students, such that a gradual incorporation of technology has seemed to become slowly but steadily more and more normalized (Bax, 2003(Bax, , 2011Goertler, 2019).…”
Section: Proficiency Development and Technology-mediated Language Ins...mentioning
confidence: 99%
See 1 more Smart Citation